Summer marine heatwaves in the South China Sea: Trend, variability and possible causes - Hong-Jian Tan; Rong-Shuo Cai; Ren-Guang Wu (Advances in Climate Change Research, 2022)
Marine heatwaves (MHWs) have been frequently observed worldwide, causing devastating impacts on marine organisms and ecosystems, but the trend of MHWs is still unclear in the South China Sea (SCS). Here, the long-term trend and inter-annual variability of the summer SCS MHW events are investigated based on the high-resolution daily satellite data. The results revealed remarkable increases in the duration, intensity, coverage, and severity during 1982–2019, indicating that the SCS MHW events have become more frequent, intense, extensive, and serious. The probability ratio of SCS MHW events is four times during the 2010s of that during the 1980s. The increasing trend can be largely attributed to the long-term increase in the mean SCS temperature. The inter-annual variability of the SCS MHWs is linked closely to the El Niño and Southern Oscillation, with more/less MHW events occurring during the following summer after the El Niño/La Niña events. A diagnosis of synoptic-scale heat budget suggests that the extreme SCS warming can be explained by the combined effects of positive surface heat flux largely due to the enhanced shortwave radiation and convergence of oceanic advection in association with an anomalous upper-ocean anticyclone. The effect of surface heat flux seems to be predominant over the large spatial coverage, whereas oceanic heat transport is also important in some specific regions. The large-scale anticyclonic circulation anomalies over the northwestern Pacific accompanying the westward-extending western Pacific subtropical high during the El Niño decay summers play an essential role in the building-up and persistence of the extreme warming, which has important implications for the prediction of the SCS MHWs.